Population Dynamics of Natural Enemies of Stem Borer Complex and their Correlation with Weather Parameters in Rice Ecosystem - Kumar, Neeraj; Sharma , Amit Kumar; Das , S. B.; Panse , R.K.; Gadekar, Manish; Seervi , Sitaram (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
A field experiment was carried out at the Murjhad Research Farm, College of Agriculture Balaghat, during Kharif 2022 and Kharif 2023 to ascertain the population dynamics of natural enemies of stem borer complex, their relative abundance and correlation with abiotic factors in order to propose ecologically and financially feasible measures. Results reveal that spiders, mirid bugs, coccinellids, odonata, staphylinids, cicindelids and carabids were the most prevalent natural enemies in the rice ecosystem. The pooled results revealed that the population of spiders was first observed during the 31st SMW (0.10 spiders/hill) with its peak during the 40th SMW (1.21 spiders/hill). Population of mirid bugs was first observed during the 31st SMW (0.45 mirid bugs/ hill) with its peak during the 39th SMW (2.45 mirid bugs/ hill). The population of adult beetles of coccinellids was first observed during the 31st SMW (0.92 ladybird beetles/sq m) with its peak during the 40th SMW (13.51 ladybird beetles/sq m). The population of adult dragonflies and damselflies was first observed during the 30th SMW (0.40 dragonflies and damselflies/sq m) with its peak during the 38th SMW (8.28 dragonflies and damselflies/sq m). The population of adult staphylinids was first observed during the 30th SMW (1.50 adults/sq m) with its peak during the 38th SMW (18.00 adults/ sq m). The population of adult cicindelids was first observed during the 32nd SMW (0.24 adults/sq m) with its peak during the 37th SMW (0.70 adults/sq m). The population of adult beetles of carabids was first observed during the 30th SMW (0.23 adults/sq m) with its peak during the 39th SMW (3.69 adults/sq m). The pooled data on relative abundance revealed that a total of 385.55 adults of natural enemies were observed throughout the crop growth. Of them, 2.39% were spiders, 3.06% were mirid bugs, 26.78% were ladybird beetles, 18.80% were odonata, 40.98% were staphylinids, 1.14% were cicindelids, 6.85% were carabid beetles. The pooled data on correlation studies revealed that population of spiders was found significantly negative correlated with evaporation and wind velocity. (r= -0.677 and -0.568, respectively) The adult population of mirid bugs found significantly positive correlated with morning RH and evening RH (r= 0.658 and 0.594, respectively). The adult population of coccinellids, odonata and staphylinids was not found significant with any whether parameters. The adult population of cicindelids found significantly positive correlated with morning RH and evening RH (r= 0.666 and 0.644, respectively). The adult population of carabids found significantly positive correlated with morning RH and evening RH (r= 0.587 and 0.545, respectively).